Effect of pH and water activity over Nomuraea rileyi (Hyphomycetes) development - AGUIRRE, NATALIA; VILLAMIZAR-R., LAURA; ESPINEL-C., CARLOS; COTES-P., ALBA MARINA (Revista Colombiana de Entomología, 2009)
The armyworm Spodoptera frugiperda causes important economical losses in corn, cotton and sorghum crops. an alternative for its control is the use of the entomopathogenic fungus Nomuraea rileyi, which causes natural epizootics in the field. At the Biological Control Laboratory of Corpoica, two mycopesticides were developed based on a native isolate of this fungus, formulated as an emulsifiable concentrate and as a dispersible granule. The insecticidal activity of the products was significantly lower than that obtained with the unformulated fungus, possibly due to the formulation, considering the high susceptibility of this fungus to abiotic factors. For this reason, the main objective of the present work was to evaluate the effect of pH and water activity (Wa) on the germination, sporulation, radial growth and insecticidal activity of N. rileyi. These parameters were evaluated by using Ym culture media adjusted to pH values from 4 to 9 and Wa values from 0.950 to 0.998. Results showed that both development and insecticidal activity of the microorganism were affected by pH, the best results being obtained with a pH range from 5 to 7. The microorganism needed high values of Wa (> 0.99) for germinating, growing and developing an infection in the insect. Results will allow the optimization of formulations, adjusting to the most adequate conditions for development and efficacy of the microorganism.